Adaptasi Karyawan Pengasuh Lansia melalui Job Crafting : Studi Kualitatif pada Pusat Pelayanan Sosial Lanjut Usia - Ferdian, Ahmad Luthfi; Yuliana, Ika; Makiah, Makiah; Cahyadi, Irwan; Marlina, Febria Nurmelia (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This study investigates the adaptation process of elderly caregivers at the Mandalika Mataram Social Welfare Institution for the Elderly (PSLU) through the application of job crafting. The main problem addressed in this research is how caregivers adjust their work relationships and responsibilities to effectively care for elderly residents with diverse emotional and behavioral characteristics. The aim is to explore how job crafting facilitates employee adaptation in challenging caregiving environments. This study employs a descriptive qualitative method, using in-depth interviews, observations, and documentation as data collection techniques. Three caregivers were selected as informants based on their experience and direct involvement in caregiving tasks. The findings reveal that caregivers at PSLU Mandalika Mataram adapt by adjusting their work relationships such as building harmonious interactions, managing conflicts, and maintaining communication with supervisors and by optimizing their job responsibilities through customized caregiving methods, effective time management, teamwork, and the creation of additional meaningful activities. These adaptation strategies not only enhance caregiving performance but also promote the psychological well-being of both caregivers and elderly residents. The study highlights the importance of job crafting as a human resource development strategy in social service institutions.